Turkey as the 'Liberator' of Muslims in Europe: The Circulation of Islamophobia as a Political Remittance - Maritato, Chiara (PARTECIPAZIONE E CONFLITTO, 2022)
This article investigates how the fight against Islamophobia both clarifies and shapes the contours of Turkey's diaspora policy. It relies on the literature on political remittances and its value to diaspora studies by highlighting to what extent and how the commitment to tackling Islamophobia plays a role in Turkey's attempt to strengthen the link with 'its' diaspora. In this process, attention is devoted to how Turkish state institutions like the Presidency of Religious Affairs (Diyanet) have framed Islamophobia as a religion-based problem and an "anti-Islamic project". In so doing, they bolster a dichotomic narrative between secular Europe and Muslim migrants. The empirical discussion also reveals the international dimension of the fight against Islamophobia and examines the Turkish government's motivation to proclaim itself the defender of (Turkish) Muslim communities in Europe. Thus, the official narrative that overlooks any systemic discriminations Turkish minorities are experiencing in everyday life has promoted a tutelary representation that might reinforce a paternalistic view of the diasporas as victims who need saving.